Simple, Yet Powerful English of MoveOns's Campaigns - Aris Munandar (Humaniora, 2012)
Getting messages across to a large audience of diverse backgrounds is a challenge. MoveOn.org is successful in responding to the challenge when writing its campaigns in a language intelligible to all members. This research studies the characteristics of English used in MoveOn’s campaigns during the periods of January 25, to March 30, 2011. It reveals that the campaigns choose ordinary words (neither politically charged nor hyperbolic) to maintain neutrality and situation-problem-solution pattern for its rhetorical structure in order to convey an easy-to-follow argument. The research concludes that MoveOn designs its campaigns to produce persuasive effects that are more rational based than emotional-based.